Radiological Evaluation of Length Discrepancy and Angular Deformity of Injured Growth Plate in Kit Rabbit Model - Hilal, Sura; K Hussein, Aseel (The Iraqi Journal of Veterinary Medicine, 2024)
Growth plate injury is one of the most significant sequelae that affect the animal and man life in adulthood. This condition considered as one of the real problem encountered by many orthopedics which can result in the formation of a bony bridge leading ultimately to limb length discrepancy and angular deformity of the long bones in kid animals. The objective of this study was to evaluate the deformities of the tibial length and angle radiographically after experimentally inducing growth plate injury. Five local breed kit rabbits included in this study, had body weight and age ranges of 500 to 1100 g and 6 to12 weeks, respectively. The animals were exposed to approximately 5×5×1 mm injury in the proximal tibial growth plate (type-III to IV classification. A radiological follow up at 1st, 2nd, 3rd and 4th week post inducing injury was made for possible evaluation of growth plate injury and calculate the length discrepancy of tibial and angular deformity by the end of the study. The radiological results revealed that bony bridge formation was clearly seen by 3rd and 4th weeks post induction. Furthermore, there were significant differences (P<0.05) in the length discrepancy of tibia started by 2nd week (P= 0.0175) and its angular deformity by 3rd week (P=0.0111) of the affected tibia limb and contralateral limb of the same animal up to the end of the study. In conclusion, the current study indicated that the formation of a bony bridge is a radiological sign of the damaged growth plate that ultimately leads to length discrepancy and angular deformity‎‎‎.